Effects of long-term almond consumption on markers for vascular function and cardiometabolic risk in men and women with prediabetes: results of a randomized, controlled cross-over trial. - Chavez-Alfaro, Marco A.; Mensink, Ronald P.; Gravesteijn, Elske; Joris, Peter J.; Plat, Jogchum (European Journal of Nutrition, 2025)
Purpose: The aim of this study was to investigate the long-term effects of almond consumption on peripheral vascular function, ambulant blood pressure profiles (ABP), and serum/plasma markers reflecting endothelial dysfunction and inflammation in participants with overweight/obesity and prediabetes. Methods: Thirty-four participants completed this single-blinded, randomized, cross-over trial with 5-month intervention and control periods, separated by a 2-month wash-out. During the intervention period, participants consumed 50 g of whole almonds daily. At the end of each intervention period, peripheral vascular function was assessed by measuring the carotid-to-femoral and carotid-to-radial pulse wave velocities (PWVc-f and PWVc-r, respectively) and retinal microvascular calibers. Serum/plasma concentrations of soluble intracellular adhesion molecule-1 (sICAM-1), soluble vascular cell adhesion molecule-1 (sVCAM-1), interleukin-6 (IL-6), IL-8, tumor necrosis factor-alpha (TNFα), serum amyloid A protein (SAA) and high-sensitivity C-reactive protein (hs-CRP) and 24-hour ABP were also analyzed. Results: Almond consumption did not significantly affect arterial stiffness (PWVc−f and PWVc−r), while central retinal venular equivalent (CRVE) was minimally increased by 2 μm (P = 0.019). Central retinal arteriolar equivalent (CRAE), the arteriolar-to-venular ratio (AVR), and endothelial and inflammatory serum/plasma markers showed no significant changes after almond consumption. Almond consumption reduced systolic blood pressure (SBP; -3 mmHg 24-hour P = 0.035, -4 mmHg daytime P = 0.046, and − 4 mmHg during nighttime P = 0.029), SBP variability during 24-hour, daytime, and nighttime (P = 0.005, P = 0.019, and P = 0.003, respectively), and diastolic blood pressure variability during nighttime (P ≤ 0.001). Conclusion: Almond consumption did not affect arterial stiffness, retinal microvasculature calibers, or serum and plasma markers for endothelial dysfunction and inflammation in participants with prediabetics, while BP and BP variability were improved. Clinical trial registration: This clinical trial was registered in February 2018 as NCT03419702.